Eye tracking in the wild: Piloting a real-life assessment paradigm for older adults - Damaris Aschwanden; Nicolas Langer; Mathias Allemand (Bern Open Publishing, 2019)
Previous research showed associations between personality traits and eye movements of young adults in the laboratory. However, less is known about these associations in real life and in older age. Primarily, there seems to be no paradigm to assess eye movements of older adults in real life. The present feasibility study thus aimed to test grocery shopping as a real-life assessment paradigm with older adults. Additionally, possible links between personality traits and eye movements were explored. The sample consisted of 38 older individuals (M = 72.85 years). Participants did their grocery shopping in a supermarket while wearing an eye tracker. Three key feasibility issues were examined, that is (1) wearability of the eye tracker during grocery shopping, (2) recording, and (3) evaluation of eye movements in a real-life context. Our real-life assessment paradigm showed to be feasible to implement and acceptable to older adults. This feasibility study provides specific practical recommendations which may be useful for fu-ture studies that plan to innovatively expand the traditional methods repertoire of personality science and aging research by using eye tracking in real life.